2008
DOI: 10.4315/0362-028x-71.7.1338
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination of Knives Used in the Meat Industry: Effect of Different Water Temperature and Treatment Time Combinations on the Reduction of Bacterial Numbers on Knife Surfaces

Abstract: Previous regulations in Australia and internationally required that knives used during the slaughter and dressing of carcasses be sanitized by brief submersion in water at 82 degrees C. Many current international regulations allow science-based equivalent alternative procedures to be used. However, limited time-temperature data are available on the response of bacteria to hot-water treatment on knives. The present study was undertaken to determine the effect of combinations of time and temperature ranging from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…Fastoperating meat processing plants may frequently experience difficulty in disinfecting meat knives with conventional cleaning techniques, where knives are hand washed in water at 20 to 40°C followed by brief immersion (less than 10 s) in 82°C water baths, termed " sterilizers." Immersions imple mented in some processing plants have been observed to be approximately 1 s, which did not have significant impact on bacterial reductions (9,25,26). On the other hand, longer immersions (10 s) of heavily contaminated knives in hot water baths often result in protein coagulations on the surface of the knives, which entrap surviving bacteria, leading to unsatisfactory bacterial reductions (26).…”
Section: Steam-ultrasound Treatment Of Conveyor Beltsmentioning
confidence: 98%
See 1 more Smart Citation
“…Fastoperating meat processing plants may frequently experience difficulty in disinfecting meat knives with conventional cleaning techniques, where knives are hand washed in water at 20 to 40°C followed by brief immersion (less than 10 s) in 82°C water baths, termed " sterilizers." Immersions imple mented in some processing plants have been observed to be approximately 1 s, which did not have significant impact on bacterial reductions (9,25,26). On the other hand, longer immersions (10 s) of heavily contaminated knives in hot water baths often result in protein coagulations on the surface of the knives, which entrap surviving bacteria, leading to unsatisfactory bacterial reductions (26).…”
Section: Steam-ultrasound Treatment Of Conveyor Beltsmentioning
confidence: 98%
“…An optimized disinfection process has to reduce microorganisms to levels considered safe from a public health of view and to reduce the count of quality damaging microorganisms (16,17). General types of disinfection methods may include thermal disinfection, using a hot water or/and steam treatment at a specific treatment time and temperature, or a chemical disinfection with a specific concentration and surface contact time (2,7,9,16,17,20,28,30). Chlorine is among the most common food industry disinfection agents that target many types of bacteria and molds.…”
mentioning
confidence: 99%
“…These data indicate that it would be sufficient with a 0.05 s treatment in 95°C water to reach complete inactivation (6 log unit reduction). In a study by Goulter, butcher knifes smeared with a meat-culture were shown to require at least 20 s at 82°C for a 5 log unit reduction (Goulter, Dykes, & Small, 2008). Taking the temperature into consideration this would indicate treatment times of 0.37 s at 95°C.…”
Section: Decontamination Testmentioning
confidence: 99%
“…Because international regulations require harvest sanitation, knives are typically sanitized with short-term immersion (1 to 5 s) in a ''knife sterilizer'' containing hot water (.82uC) (8). Previous studies aiming to validate different knife sanitations have shown promising alternatives to standard thermal sanitation.…”
mentioning
confidence: 99%
“…Similarly, Salmonella Typhimurium DT104 was reduced by 2.39, 1.49, and 1.66 log CFU/cm 2 after a 15-s treatment with hot water (82.2uC), 440 ppm of 4-alkyl QAC, and 440 ppm of 4-alkyl acid QAC, respectively (18). Goulter et al (8) evaluated E. coli O157:H7 and Listeria monocytogenes reductions on knives dipped in water for 42 time-temperature treatment combinations. The authors concluded that short dips in hightemperature water (i.e., 82uC water for 1 s) reduce pathogen populations equivalent to a dip in lower temperature water for a longer time.…”
mentioning
confidence: 99%